Investigation of sensor probe performance on soil moisture conditioning monitoring system - Nik Adham Faris, Nik Azan Rasul; Muhammad Arif, Osman; Aisyah Illani, Sulaiman; Roshahliza, M. Ramli; Nadzirah, Mohd Mokhtar (Springer Singapore, 2024)
The Internet of Things (IoT) is continuously advancing with improved internet technology, providing new opportunities for innovation such as in agriculture that can benefit from IoT devices. This paper focuses on investigating the performance of a sensor probe in an environmental conditioning monitoring system. The project aims to develop an IoT-based moisture sensor capable of collecting and storing data on the cloud using a cloud server. This study explores optimal conditions for accurate data collection and analyzes the sensor’s performance in different soil conditions, including dry, waterlogged, and normal. A wireless sensor network integrated with the moisture sensor is designed and implemented for real-time data collection through the IoT infrastructure. Then, the acquired information is stored on a cloud platform. With varying soil conditions, the sensor’s performance is thoroughly examined, providing insights into its accuracy and reliability. This knowledge is valuable for effective strategies in agriculture and water resource management, improving decision-making and resource allocation. The research contributes to the advancement of environmental conditioning monitoring systems, informing the development of enhanced sensor technologies, and promoting more efficient and sustainable agricultural practices, with the potential to enhance the growth of crops. By providing real-time and precise data on environmental conditions, the improved monitoring systems and sensor technologies enable farmers to optimize their crop management strategies, ensuring that crops receive the ideal conditions for growth. This heightened level of environmental control and management can lead to increased crop yields, improved crop quality, and overall enhanced agricultural productivity.